United Nations Sustainable Development Goals - marketing solutions for a technological and innovation focused engineering company. - Balakrishnan, Narainthiran (2018)
The recent glut in the oil& gas industry has resulted in many economies to collapse, many companies to close and thousands of people to lose their job. This has raised questions on the traditional and conventional practices in the industry. At the same time, innovation and technological advances has become synonym with companies that have remained successful in the business. It has been widely researched that innovative is an important source of competitive advantage for firms to be successful. In addition to the recent oil crisis, another pressing issue is the concerns that oil & gas exploration and production is causing harm to the environment. The United Nations have always addressed their concerns on the worrying environmental situation. This together with other goals to bring improvement to society has been addressed in 2015 via the United Nations Sustainable Development Goals (UNSDG).